Health Literacy Profiles of Early Intervention Providers: Use of the Health Literacy Questionnaire - Catherine J. Leslie; Karen Donelan; Patrice Nicholas; Maura Buglione; Diane L. Smith (Health Literacy Research and Practice, 2022)
Background: Early intervention (EI) providers work with parents of children with or who have risk factors of developmental delay or disability through Part C of the Individuals with Disabilities Education Act. Many parents in the United States have low health literacy; therefore, EI providers should be aware of and address families' health literacy needs. EI providers need to be health literate themselves to implement evidence-based recommended practices. Objective: This study aimed to measure health literacy levels of interdisciplinary EI providers and investigate associations between health literacy levels and demographic variables. Methods: A survey containing the Health Literacy Questionnaire (HLQ) was completed by EI providers working at 10 EI centers in Massachusetts. Scale scores were calculated and compared across demographic variables, including EI job role, age, years of EI experience, and highest education level. Key Results: Of 715 EI providers invited to participate, 376 surveys were completed (52.6% response rate). Most participants were women (92.6%, n = 348), reported race as White (85.4%, n = 321), had a mean age of 43.1 years (standard deviation [SD] 12.9) ranging from 20 to 74 years, and English as their primary language (89.6%, n = 337). EI providers scored the lowest on HLQ Scale 5 “Appraisal of health information” (mean [M] = 2.99 (SD 0.50) [confidence interval (CI) 2.93, 3.04]), and Scale 7 “Navigating the healthcare system” (M = 3.83 (SD 0.58) [CI 3.77, 3.89]). EI providers having stronger health literacy profiles were generally older, with a higher education level, were licensed providers, or had more years of EI work experience. Conclusions: EI providers require adequate health literacy to manage their health needs and to effectively provide services to EI families. Study results may inform future targeted professional development to support improvement of EI providers' health literacy skills, including appraisal of health information and navigation of the health care system. [HLRP: Health Literacy Research and Practice. 2022;6(2):e128–e136.] Plain Language Summary: EI providers' health literacy profiles have not been previously investigated. Study results reveal EI providers struggled with health literacy skills of appraising health information and navigating the health care system, which are vital for EI practice. Health Literacy Questionnaire results can inform targeted professional development to improve EI providers' health literacy levels and their clinical practice.